The Relationship Between Information and Self-Care Management in Leprosy Patients - Mujib Hannan; Cory Nelia Damayanti; Syaifurrahman Hidayat (GLOBAL HEALTH SCIENCE GROUP, 2025)
Leprosy is still a health problem in endemic countries, one of which is Indonesia. It is caused by the lack of information about leprosy, which affects the self-care management of leprosy sufferers to increase the risk of leprosy severity. Leprosy is a chronic granular infection caused by the obligate intracellular organism M. leprae. These germs initially attack the peripheral nervous system, then the skin, mucosa, respiratory tract, retinal system, eyes, retina, bones, and tissues. This study aims to determine the relationship of information on self-care management in leprosy patients in the Sumenep Regency. This type of research was an observational analysis using a cross-sectional study approach. The population was 32 respondents, with a sample of 30 respondents. The sampling technique used simple random sampling. Data collection used a questionnaire, and data analysis used Rho Spearman with a significance level of p<0.005. The analysis result obtained significance, or the value of information availability (0.000) was much more standard significant than 0.05 or (p < a), then H0 was rejected, and H1 was accepted, which means that there is a relationship between information and self-care management in leprosy patients. Information can affect self-care management in leprosy patients. Self-care management has an important role in preventing the severity and transmission of leprosy. With enough information, leprosy patients can carry out good self-care- management and reduce the impact of leprosy effectively.